Estimating somatic maturity in adolescent soccer players: Methodological comparisons - Salter, J.; Cumming, S.; Hughes, J. D.; De Ste Croix, M. (International Journal of Sports Science & Coaching, 2022)
Purpose: Monitoring maturation facilitates effective talent development. Various methods of maturity estimation exist with limited knowledge of concordance between methods. This study aims to establish agreement between methods of varied constructs to predict maturity status and compare concordance of methods to categorise players using established thresholds.Methods: This study compared four maturity equations using anthropometrical data from 113 male adolescent soccer players (mean SD; age, 14.3+-1years) from two academies. Conservative (+-1year) and less conservative (+-0.5years) circa-PHV thresholds were employed. Results: Analysis indicates tight (0.3 year) agreement between maturity offset methods (MO), but broader agreement between MO and predicted adult height methods (-1.5 to 1 year). However, Kappa Cohen k suggests moderate to substantial (44%-67%) and fair to moderate (31%-60%) concordance between methods when using the conservative and less conservative circa-PHV thresholds respectively. Conclusion: Despite MO equation iterations claiming to reduce systematic error, they provide very similar estimations. Additionally, practitioners should not use maturity offset and predicted adult height methods interchangeably and are encouraged to apply either method consistently when looking to estimate maturity status or biologically calssify players.